MANAGEMENT ANALYSIS OF AGRIBUSINESS DEVELOPMENT STRATEGY FOR NATIVE PIGS AND CHICKENS IN MANGGARAI REGENCY, NTT - H. D., TUKAN; NUGRAHA, E. Y.; DALLE, N. S.; UTAMA, W. G.; SIKONE, H. Y.; SIKONE, H. Y. (Majalah Ilmiah Peternakan; Vol 27 No 2 (2024): Vol. 27 No. 2 (2024)DO - 10.24843/MIP.2024.V27.i02.p01, 2024)
The purpose of this study is to analyze the feasibility of investment from financial and non-financial aspects and find out the formulation of development strategies to increase competitiveness. This research will take place from February to April 2023 in Manggarai district, NTT province. This research uses methods: qualitative, desc- riptive and quantitative. Based on the results and discussion in the study, it can be concluded that this business has met the requirements and is feasible to be pursued because it is able to produce an average nominal received of IDR.4,600,000.00 in the pig farming business and IDR.900,000.00 in the native chicken farming business and the achievement of the business return point running for 1.22 years in pigs and 4.76 years in native chickens. The results of the identification of internal and external factors are very supportive such as socio-cultural aspects or customary customs of the community, the potential availability of feed greatly supports livestock production. The policy formulation produces 7 (seven) strategic management options that must be prioritized in the development of native pig and chicken agribusiness in Manggarai district.